2019
DOI: 10.1186/s40246-019-0212-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide enriched pathway analysis of acute post-radiotherapy pain in breast cancer patients: a prospective cohort study

Abstract: Background: Adjuvant radiotherapy (RT) can increase the risk of developing pain; however, the molecular mechanisms of RT-related pain remain unclear. The current study aimed to identify susceptibility loci and enriched pathways for clinically relevant acute post-RT pain, defined as having moderate to severe pain (pain score ≥ 4) at the completion of RT. Methods: We conducted a genome-wide association study (GWAS) with 1,344,832 single-nucleotide polymorphisms (SNPs), a gene-based analysis using PLINK set-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway database and Gene Ontology (GO) database under biological process and molecular function categories were used for functional annotation and enrichment analyses. Over-representation of genes in every GO terms and pathways were tested using a Fisher's exact test, which was conducted using the web-based gene-enrichment analysis tool, the Database for Annotation, Visualization, and integrated discovery (DAVID, http://david.abcc.ncifcrf.gov/) [32]. False discovery rate (FDR) correction (<0.05) was applied to account for multiple testing [32].…”
Section: Gene-set Enrichment and Pathway Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway database and Gene Ontology (GO) database under biological process and molecular function categories were used for functional annotation and enrichment analyses. Over-representation of genes in every GO terms and pathways were tested using a Fisher's exact test, which was conducted using the web-based gene-enrichment analysis tool, the Database for Annotation, Visualization, and integrated discovery (DAVID, http://david.abcc.ncifcrf.gov/) [32]. False discovery rate (FDR) correction (<0.05) was applied to account for multiple testing [32].…”
Section: Gene-set Enrichment and Pathway Analysismentioning
confidence: 99%
“…Over-representation of genes in every GO terms and pathways were tested using a Fisher's exact test, which was conducted using the web-based gene-enrichment analysis tool, the Database for Annotation, Visualization, and integrated discovery (DAVID, http://david.abcc.ncifcrf.gov/) [32]. False discovery rate (FDR) correction (<0.05) was applied to account for multiple testing [32]. The GO terms/KEGG category pathways with more than 10 and less than 1000 genes were analyzed for narrowing down the functional categories.…”
Section: Gene-set Enrichment and Pathway Analysismentioning
confidence: 99%
“…It has been reported that the ZNF429 gene is signi cantly associated with acute postoperative pain in breast cancer, whereas ZNF208 polymorphisms are associated with ischemic stroke in a southern Chinese Han population. [40,41] Studies have found that PABPC1 (poly(A) binding protein cytoplasmic 1) is directly involved in the tumorigenesis of gastric cancer through promotion of cell proliferation; consistent with this, down-regulated expression of PABPC1 is associated with tumor progression and a worse prognosis. [42,43] Our analysis of the TCGA-THYM database further showed that the genes with the highest mutation frequency were GTF2I (50%), HRAS (8%), and MUC16 (7%) (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Olfr plays an important role in many physiological and pathological processes such as sensory perception, behavior and emotion regulation, immune system activity and inflammation regulation, tumor growth, and metastasis ( Meijerink, 2021 ). Although there were few studies on its mechanism of action in hyperalgesia, the current research status suggests that it is closely related to hyperalgesia in certain diseases ( Lee et al., 2019 ). The genome-wide association study of blood samples from breast cancer patients showed that the occurrence of pain after adjuvant radiotherapy was significantly associated with the activity of Olfr genes (OR52N1, OR4C12, OR4A47) ( Lee et al., 2019 ).…”
Section: The Interaction Of Hyperalgesia-related Receptors In Ecs With Intestinal Flora and Its Metabolitesmentioning
confidence: 99%